Of mice, genes, and radiation: the genetics of non-hereditary breast cancer explored using the common laboratory BALB/c mouse - Ramaiah, Lila, author; Ullrich, Robert L., advisor; Benjamin, Stephen A., advisor (Colorado State University. Libraries, 2008)
In this dissertation we describe the generation and characterization of two novel strains of mice carrying alternate genetic variants of the DNA repair gene Prkdc (DNA-PKcs). Strains congenic for the common (PrkdcB6) and variant (Prkdc BALB) alleles of Prkdc are developed, genotypically validated, and used to examine the functional consequences of Prkdc BALB and its linkage with radiation susceptibility. DNA-PKcs protein expression, post-irradiation double strand break repair, post-irradiation cell survival, breeding depression, and constitutive and radiation-induced gene expression are examined. By western blot we demonstrate that PrkdcBALB is required and sufficient to decrease DNA-PKcs protein expression. Using three different DSB repair quantification methods we show that PrkdcBALB is required for reduced radiation-induced DSB rejoining in BALB/c. We also show that Prkdc BALB is both sufficient and required for decreased cell survival after exposure to ionizing radiation. Thus we demonstrate that Prkdc BALB modulates and even diminishes the ability of cells to maintain genomic homeostasis. Using our newly developed congenic mice, we present the first evidence that PrkdcBALB has a significant effect on gene expression in unirradiated as well as irradiated mice. Microarray analysis of gene expression reveals that PrkdcBALB may have a greater impact on overall gene expression than does radiation, and that Prkdc may play a role in constitutive and DNA damage-induced apoptotic and transcriptional responses. The results presented within this dissertation support the hypothesis that the main role of PrkdcBALB in radiation-induced breast cancer is the initiation of mammary epithelial cells. Our data show that PrkdcBALB is strongly associated with diminished DNA-PKcs expression and function, diminished survival, and altered transcriptional regulation. The congenic strains developed and characterized in this proposal will be instrumental in ongoing studies aiming to clarify the role of Prkdc and genomic instability in radiation-induced mammary carcinogenesis in the BALB/c mouse. Future studies should endeavor to quantify DNA-PKcs specific kinase activity and protein metabolism and to evaluate cytogenetic instability, with particular emphasis on telomeres. The congenic strains developed and characterized in this work serve as compelling rodent models of sporadic and radiation-induced human breast cancer, and provide proof of principle for the role of genetic polymorphisms and genomic instability in breast cancer susceptibility.
Keywords: BALB; breast cancer; DNA repair; DNA-dependent proteins; polymorphism; radiation; genetics; pathology; oncology